Email Intervention Following Traumatic Brain Injury: Two Case Reports - Min Jung Kim; Julie A.G. Stierwalt; Leonard L. LaPointe (International Journal of Telerehabilitation)
An email intervention for two individuals with TBI was conducted to investigate if this electronic medium would show potential as a therapeutic delivery method. Specifically, this study measured participants’ compliance to a plan that incorporated email and a reading assignment. Prior to the email intervention, a clinician and participants designed an intervention plan, which included specific guidelines for scheduled email correspondence regarding a daily reading task. After reviewing the daily emails the clinician provided therapeutic feedback. The participants’ compliance to the plan was measured by punctuality of email correspondence and completion of tasks as detailed in the plan. Over a 4-week intervention period, both participants demonstrated improvement in task completion and time adherence. With these individuals, email proved to be a feasible option as a therapeutic delivery method.      Keywords: email intervention, individuals with TBI, task completion, time adherence